Dabigatran etexilate for stroke prevention in patients with atrial fibrillation: Resolving uncertainties in routine practice - Huisman, Menno V.; Lip, Gregory Y. H.; Diener, Hans-Christoph; Brueckmann, Martina; van Ryn, Joanne; Clemens, Andreas (Thrombosis and Haemostasis, 2012)
Dabigatran etexilate is a new oral anticoagulant recently approved in Europe for the prevention of stroke or systemic embolism in adult patients with non-valvular atrial fibrillation (AF) and at least one risk factor for stroke. With a fast onset of action and a predictable anticoagulant effect obviating the need for coagulation monitoring, dabigatran etexilate offers practical advantages over vitamin K antagonists in clinical practice. However, clinicians may have questions about practical aspects of dabigatran etexilate use including monitoring anticoagulant efficacy, interruption for surgical or invasive procedures and management of bleeding. This review article aims to address these concerns and provide guidance on the use of dabigatran etexilate in special situations, such as acute coronary syndromes and cardiac revascularisation. In addition, cut-off values for different coagulation assay results associated with an increased risk of bleeding are given.Note: The editorial process for this article was fully handled by Prof. Christian Weber, Editor-in-Chief.
Keywords: Dabigatran; atrial fibrillation; oral anticoagulant; bleeding